Learning, Design, and Technology 2016
DOI: 10.1007/978-3-319-17727-4_35-1
|View full text |Cite
|
Sign up to set email alerts
|

Do You Have a SOLE? Research on Informal and Self-Directed Online Learning Environments

Abstract: Web-based resources and technologies for informal and self-directed learning have proliferated during the past two decades. This chapter reviews some of the key research on informal and self-directed learning. Next, it explores different types of informal and self-directed online learning environments (SOLEs) (e.g., learning portals, shared online video, language learning, adventure learning, virtual learning, global change, etc.). An eight-part scheme for analyzing the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…How does one study SDOL? As online resources proliferate and access to the Internet continues to increase, whether on a desktop computer, laptop, phone, or watch, SDOL is happening all around with every step one takes in a city, including when seated at a special event, strolling through a park, or while traversing the campus of an educational organization or institution (Bonk et al, 2016). Do you ever watch online learners on their laptops with headsets when in an airport hangar or when seated in a local cafe?…”
Section: Locating the Trailheadmentioning
confidence: 99%
See 2 more Smart Citations
“…How does one study SDOL? As online resources proliferate and access to the Internet continues to increase, whether on a desktop computer, laptop, phone, or watch, SDOL is happening all around with every step one takes in a city, including when seated at a special event, strolling through a park, or while traversing the campus of an educational organization or institution (Bonk et al, 2016). Do you ever watch online learners on their laptops with headsets when in an airport hangar or when seated in a local cafe?…”
Section: Locating the Trailheadmentioning
confidence: 99%
“…However, we chose a different approach. After the publication of his book, The World Is Open: How Web Technology Is Revolutionizing Education, Bonk (2009) recruited a large team of 20 researchers to explore the human learning and development potential of more than 300 informal learning websites (Bonk et al, 2016;Kim et al, 2014;Song & Bonk, 2016). These resources are typically related to six areas: (1) language learning (which has exploded over the past decade); (2) outdoor and adventure learning; (3) social change and global forms of learning;…”
Section: Retracing One's Stepsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors identified a need for additional research studies examining learners' psychological decision-making process when they lower performance aspirations or alter their online learning goals. Most of the studies in their review focused on formal and informal help-seeking strategies, which is not surprising given the proliferation in ways to learn informally and self-direct one's own learning during the early decades of the 21 st century (Bonk, 2009(Bonk, , 2016Bonk et al, 2016). Significantly, these authors call for generalizable studies rather than small case studies.…”
Section: Help-seeking Strategiesmentioning
confidence: 99%
“…By understanding the video seeking behavior in a situated context, more effective video interfaces can be developed. In SDL, the process of finding and evaluating resources is integral as learners have autonomy over their learning (Bonk, Kim, & Xu, 2016;Butcher & Sumner, 2011). Understanding the video seeking behavior of adolescent learners in a situated context can offer insights to address research question 1 and 3 as put forth in Chapter 1:…”
Section: Aims Of the Studymentioning
confidence: 99%